Pengaruh Kualitas Laporan Keuangan terhadap Kepercayaan Publik di Lingkungan Pemerintah Provinsi Sumatera Barat - Jovan Alfredo Shaquille; Alex Djan Serumi Kawer; Muhammad Alvin Brilian Ankares; Muhammad Rafi Tri Saputra; Arina Romarina (BADAN PENERBIT STIEPARI PRESS, 2026)
This study aims to analyze the influence of financial report quality on public trust in the Government of West Sumatra Province. The background of this research stems from the importance of transparency and accountability in regional financial management as the foundation for building public legitimacy toward government performance. This research employs a descriptive qualitative method using field studies through interviews and questionnaires distributed to 55 respondents consisting of citizens, academics, and regional government officials. The results show that the quality of financial reports has a positive relationship with public trust. Openness and information relevance emerge as the most influential factors contributing to the improvement of public confidence, while understandability remains a major challenge since financial reports are often considered too technical and difficult for non-accounting audiences to comprehend. These findings emphasize that the quality of financial reports depends not only on data accuracy but also on the government’s ability to communicate information clearly and transparently. Therefore, local governments need to strengthen their public communication strategies, simplify the language of financial reports, and expand the presentation format of financial information to make it more accessible and understandable to the public. Such efforts are expected to enhance public trust and support the realization of good governance within the West Sumatra Provincial Government.